2021
DOI: 10.1101/2021.03.23.21254003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computerized Cognitive Training in People with Depression: A Systematic Review and Meta-analysis of Randomized Clinical Trials

Abstract: Importance: Cognitive impairment is a common feature of both symptomatic and remitted states of depression that is associated with poorer psychosocial outcomes and treatment non-response. As such, finding treatments to maintain or enhance cognition in people with depression is imperative. Objective: To investigate the efficacy of computerized cognitive training (CCT) on cognitive and functional outcomes in people with depression. Data Sources: MEDLINE, EMBASE and PsycINFO databases were screened through the O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 87 publications
1
16
0
Order By: Relevance
“…The effects from this meta-analysis are similar in size compared with previous metaanalyses examining the effects of cognitive training (e.g. Launder et al, 2021;Motter et al, 2016), resulting in small to medium effect sizes for the effects of CCT. This leads to several interesting conclusions.…”
Section: Discussionsupporting
confidence: 67%
“…The effects from this meta-analysis are similar in size compared with previous metaanalyses examining the effects of cognitive training (e.g. Launder et al, 2021;Motter et al, 2016), resulting in small to medium effect sizes for the effects of CCT. This leads to several interesting conclusions.…”
Section: Discussionsupporting
confidence: 67%
“…[47][48][49] Cognitive functioning of patients with (remitted) MDD can be improved by NCRT. [52][53][54][55][56] Therefore, this study will examine the effectiveness of a multimodal approach, that is, adding oNCRT to PCT in a pragmatic RCT. To our knowledge, the current study is the first to assess if augmenting oNCRT to PCT further reduces depressive symptoms in partially remitted depressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses demonstrated that NCRT enhances attention, processing speed, executive functioning, working memory and verbal memory in (remitted) depressed patients. [52][53][54][55][56] For patients in partial remission specifically, NCRT improved attention. 57 NCRT also decreased depressive symptomatology in patients with (remitted) MDD, 52 54-56 although the robustness of the effect on depressive symptomatology is questionable as the beneficial effect disappeared when only high-quality studies were included.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…WM has been suggested as a target for enhancing cognition through CWMT (Webb et al, 2018 ; Motter et al, 2019 ). Recent studies indicate that the improvements appear in depressive symptoms, EF, and PS, following training (Barkus, 2020 ; Launder et al, 2021 ; Woolf et al, 2021 ), but results are mixed with studies including higher symptom levels showing most symptom improvement (Legemaat et al, 2021 ), and the underlying mechanisms in improvements are largely unknown (Webb et al, 2018 ; Motter et al, 2019 ; Ferrari et al, 2021 ). Given these mixed results (Lengvenyte et al, 2020 ; Legemaat et al, 2021 ), investigating depressive symptoms following CWMT with particular focus on subjective cognition seem important.…”
Section: Introductionmentioning
confidence: 99%